A cyano-based electron-accepting building block to design n-type conjugated polymers with absorption wavelength of >1000 nm. Issue 11 (19th January 2023) - Wang, Yinghui; Meng, Bin; Liu, Jian; Zhu, Feng; Qin, Chuanjiang; Liu, Jun; Wang, Lixiang
Abstract : A cyano-based electron-accepting building block to design n-type conjugated polymers with ultra-narrow optical gap. Abstract : There are much fewer n-type conjugated polymers than p-type counterparts because of the lack of strong electron-accepting building blocks. We report a novel strong electron-accepting unit based on a dicyanomethylene unit. The resulting polymers exhibit LUMO energy levels of as low as −4.04 eV and narrow optical gaps with an onset absorption wavelength of 1050 nm. Moreover, the polymers exhibit near-infrared light absorption with good photostability because of their low-lying LUMO/HOMO energy levels.